Analisis Pengaruh Sikap Pada Perluasan Merek Terhadap Minat Beli Produk Sikat Gigi Pepsodent di Kota Semarang - Fitria Ridho Utami; I Made Sukresna (Journal of Economics and Business, 2021)
The competition in dental and oral care products industry is increasing over time. Therefore, companies must have new strategies in marketing their products, for example by brand extension. The purpose of this study is to determine the effect of attitudes towards brand extension towards buying interest in Pepsodent toothbrush products in Semarang. The population in this study are Pepsodent consumers in Semarang who use toothbrush products and other products from Pepsodent. The number of samples used was 209 people who were selected using purposive sampling through a questionnaire. The data obtained is then analyzed using the AMOS program. The results of the study showed that familiarity and perceived fit variables had a positive effect on attitudes toward brand extension. While the perception of quality and innovativeness variables have no effect on the attitude towards brand extension variable. And the dependent variable, attitude towards brand extension has an effect on purchase intention. The most influential process for increasing consumers purchase intention in Pepsodent toothbrush products is by increasing perceived fit that affect attitudes toward brand extension which will increase purchase intention.